Estudo preliminar sobre a conservação do mel de cacau - Marcondes Borges , José; de Paula Pereira , Vicente (Revista Ceres, 2025)
The quick deterioration of the jelling power of cacao "sweatings" is the major handicap of increasing cacao jelly production. With this degradation occurring within 10 hours only fresh "sweating" can be used in jelly manufacture, restricting its use to farms close to the factories. Heat treatment (100°C for times between 30 and 90 seconds) has been found to extend the useful life of the "sweatings" from one day to one year. No noticeable differences were found between jellies made from "sweatings" up to six months old and the controls using fresh "sweatings". However, less consistency was noted in the jellies using six month to twelve month old "sweatings'.